Coarse Particulate Matter (PM(2.5–10)) Affects Heart Rate Variability, Blood Lipids, and Circulating Eosinophils in Adults with Asthma - Yeatts, Karin (National Institute of Environmental Health Sciences, 2007)
INTRODUCTION: We investigated whether markers of airway and systemic inflammation, as well as heart rate variability (HRV) in asthmatics, change in response to fluctuations in ambient particulate matter (PM) in the coarse [PM with aerodynamic diameter 2.5–10 μm (PM(2.5–10))] and fine (PM(2.5)) size range. METHODS: Twelve adult asthmatics, living within a 30-mile radius of an atmospheric monitoring site in Chapel Hill, North Carolina, were followed over a 12-week period. Daily PM(2.5–10) and PM(2.5) concentrations were measured separately for each 24-hr period. Each subject had nine clinic visits, at which spirometric measures and peripheral blood samples for analysis of lipids, inflammatory cells, and coagulation-associated proteins were obtained. We also assessed HRV [SDNN24HR (standard deviation of all normal-to-normal intervals in a 24-hr recording), ASDNN5 (mean of the standard deviation in all 5-min segments of a 24-hr recording)] with four consecutive 24-hr ambulatory electrocardiogram measurements. Linear mixed models with a spatial covariance matrix structure and a 1-day lag were used to assess potential associations between PM levels and cardiopulmonary end points. RESULTS: For a 1-μg/m(3) increase in coarse PM, SDNN24HR, and ASDNN5 decreased 3.36% (p = 0.02), and 0.77%, (p = 0.05) respectively. With a 1-μg/m(3) increase in coarse PM, circulating eosinophils increased 0.16% (p = 0.01), triglycerides increased 4.8% (p = 0.02), and very low-density lipoprotein increased 1.15% (p = 0.01). No significant associations were found with fine PM, and none with lung function. CONCLUSION: These data suggest that small temporal increases in ambient coarse PM are sufficient to affect important cardiopulmonary and lipid parameters in adults with asthma. Coarse PM may have underappreciated health effects in susceptible populations.